SPOR Proteins Are Required for Functionality of Class A Penicillin-Binding Proteins in Escherichia coli - Manuel Pazos (American Society for Microbiology, 2020)
ABSTRACT Sporulation-related repeat (SPOR) domains are present in many bacterial cell envelope proteins and are known to bind peptidoglycan. Escherichia coli contains four SPOR proteins, DamX, DedD, FtsN, and RlpA, of which FtsN is essential for septal peptidoglycan synthesis. DamX and DedD may also play a role in cell division, based on mild cell division defects observed in strains lacking these SPOR domain proteins. Here, we show by nuclear magnetic resonance (NMR) spectroscopy that the periplasmic part of DedD consists of a disordered region followed by a canonical SPOR domain with a structure similar to that of the SPOR domains of FtsN, DamX, and RlpA. The absence of DamX or DedD decreases the functionality of the bifunctional transglycosylase-transpeptidase penicillin-binding protein 1B (PBP1B). DamX and DedD interact with PBP1B and stimulate its glycosyltransferase activity, and DamX also stimulates the transpeptidase activity. DedD also binds to PBP1A and stimulates its glycosyltransferase activity. Our data support a direct role of DamX and DedD in enhancing the activity of PBP1B and PBP1A, presumably during the synthesis of the cell division septum. IMPORTANCE Escherichia coli has four SPOR proteins that bind peptidoglycan, of which FtsN is essential for cell division. DamX and DedD are suggested to have semiredundant functions in cell division based on genetic evidence. Here, we solved the structure of the SPOR domain of DedD, and we show that both DamX and DedD interact with and stimulate the synthetic activity of the peptidoglycan synthases PBP1A and PBP1B, suggesting that these class A PBP enzymes act in concert with peptidoglycan-binding proteins during cell division.